Detecção sorológica da leptospirose, toxoplasmose e leishmaniose em tatus-peba (Euphractus sexcinctus) de vida livre - Fernandes, Werona de Oliveira Barbosa (Universidade Federal Rural do Semi-Árido, 2015)
The increasing contact between humans and domestic animals with wild animals has contributed to spread infectious agents, thus increasing the risk of transmission of zoonosis. Therefore, this present study aimed to detect, using different serological techniques, the presence of anti-Leptospira spp., anti-Toxoplasma gondii and anti-Leishmania infantum in six-banded armadillos. For this, was used 33 species of wildlife armadillos Euphractus sexcinctus of both sexes and various ages from the city of Mossoró, Rio Grande do Norte, Brazil. Of the 33 animals subjected to serological analysis, 2/33 (6.06%) were positive for leptospirosis, where serovars reagents were Canicola and Andamana, and both with titration of 200. For the toxoplasmosis research it was noted that 2/33 (6.06%) had antibodies to Toxoplasma gondii, and all of them having the title equal to 400. In relation to leishmaniasis, 3/33 (9.09%) animals were reactive to Leishmania infantum antigen, which had the title of 320. This was the first evidence of Leishmania infantum in six-banded armadillo already described. From the present study, we can confirm the real possibility of these animals act as carriers agent with zoonotic potential
Detection of anti-leptospira spp., anti-toxoplasma gondii and anti-leishmania infantum antibodies in free range six-banded armadillo (Euphractus sexcinctus)
Keywords: Tatu - peba; Six-banded armadillo - Leishmaniasis; Zoonoses; Leptospirosis; Toxoplasmosis; Tatu - peba; Euphractus sexcinctus - Leishmaniose; Zoonoses; Leptospirose; Toxoplasmose; CIENCIAS AGRARIAS::MEDICINA VETERINARIA